2005
DOI: 10.1007/s00330-004-2532-9
|View full text |Cite
|
Sign up to set email alerts
|

The skull base: tumoral lesions

Abstract: Many lesions occur in the anterior, central and posterior skull base. In order to detect and characterise them, one has to apply the best imaging technique. Today MR is the preferred technique, and the use of CT is more and more restricted to evaluate the presence of calcifications and involvement of thin bony walls, foramina and fissures. However, MR is only superior when the right sequences and imaging planes are used. Many lesions can be characterised by their specific signal intensity on different sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
15

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 13 publications
0
17
0
15
Order By: Relevance
“…It has been suggested that EPAs could arise along the cranial migration route of Rathke's pouch toward the hypothalamus, after its development as an invagination of the primitive oral cavity during the third week of gestation; remnants of this pharyngopituitary canal in bone areas, for example, could explain EPAs in the clivus or sphenoid bone 4,5 . Surgical resection of the adenoma causing acromegaly has been the traditional approach, although normalization of IGF-1 and GH levels is observed in only 40-70% of patients 1 …”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that EPAs could arise along the cranial migration route of Rathke's pouch toward the hypothalamus, after its development as an invagination of the primitive oral cavity during the third week of gestation; remnants of this pharyngopituitary canal in bone areas, for example, could explain EPAs in the clivus or sphenoid bone 4,5 . Surgical resection of the adenoma causing acromegaly has been the traditional approach, although normalization of IGF-1 and GH levels is observed in only 40-70% of patients 1 …”
Section: Discussionmentioning
confidence: 99%
“…Chordomas present as expansile clival tumours, often exhibiting an aggressive pattern of bone destruction with replacement of the clivus bone marrow and erosion of its cortical margins. 29 On MRI, they are typically T1 isointense to hypointense and T2 isointense to hyperintense lobulated masses (Fig. 12) showing heterogenous Gadolinium enhancement.…”
Section: Chordoma Chordoma Is a Histologically Benign Butmentioning
confidence: 99%
“…MR görüntüleme, lezyonun yumuşak doku bileşenini ve çevre yapılar ile ilişkisini değerlendirmek için tercih edilen inceleme yöntemi olup, tümörün intrakraniyal uzanımını (dural, leptomeningeal, beyin parankimi invazyonunu), perinöral ve perivasküler yayılımını ve kemik iliğini tutulumunu göster-mede doğruluğu en yüksek modalitedir [2,6]. BT ise kafa tabanının kemik anatomisini gös-termede tercih edilen görüntüleme tekniğidir.…”
Section: Görüntüleme Modaliteleriunclassified
“…Kemikte ekspansiyona yol açar, nöral foramen ve fissür-lerde daralma veya yer değiştirmeye neden olabilir. Ancak, lezyon kemiğin genel şeklini ve konturlarını takip eder (Resim 4) [6]. MR'de aktif fibröz displazi lezyonları, T2A'da yük-sek sinyalli kistik alanlar içerebilir ve yoğun kontrastlanabilirler.…”
Section: Kafa Kaidesinin Tüm Bölümlerinde İzlenebilen Tümörlerunclassified